Sri Lanka Student Assessment : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
In 2012, Sri Lanka joined the Russia Education Aid for Development (READ) trust fund program, the goal of which is to help countries improve their capacity to design, carry out, analyze, and use assessments for improved student learning. As part of the READ trust fund program, and in order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Tajikistan participated in a formal exercise to benchmark its student assessment system under The World Bank's Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. SABER-student assessment is a component of the SABER program that focuses specifically on benchmarking student assessment policies and systems. The goal of SABER-student assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all. The importance of assessment is linked to its role in: providing information on levels of student learning and achievement in the system; monitoring trends in education quality over time; supporting educators and students with real-time information to improve teaching and learning; and holding stakeholders accountable for results. The SABER-student assessment framework is built on the available evidence base for what an effective assessment system looks like. The framework provides guidance on how countries can build more effective student assessment systems. The framework is structured around two main dimensions of assessment systems: the types/purposes of assessment activities and the quality of those activities. Assessment systems tend to be comprised of three main types of assessment activities, each of which serves a different purpose and addresses different information needs. These three main types are: classroom assessment, examinations, and large scale, system level assessments. This report focuses specifically on policies in the area of student assessment.